The Impact of the Fear of Missing Out (FOMO) Phenomenon on Impulsive Purchasing Decisions in Generation Z - Benny Gratianus Ndruru; Anna Pilima Bulolo; Amanat Hati Halawa; Yudita G. Ndruru; Helpianus Dachi (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
The rapid development of digital technology and social media has significantly transformed consumption behavior, particularly among Generation Z as digital natives. One psychological phenomenon emerging from intensive digital interaction is Fear of Missing Out (FOMO), defined as anxiety arising from the perception of missing valuable information, trends, or social experiences. This study aims to analyze the influence of FOMO on impulsive buying decisions among Generation Z. A descriptive qualitative approach was employed through a literature review, supported by interview, observation, and documentation data. The findings reveal that FOMO functions as a dominant psychological factor driving impulsive buying behavior, particularly through social media exposure and digital marketing strategies emphasizing urgency and scarcity. Impulsive buying is interpreted as an emotional response intended to reduce social anxiety and maintain personal relevance within digital environments. The results indicate that, in the absence of adequate self-regulation and digital literacy, Generation Z is vulnerable to excessive consumption patterns that may negatively affect financial stability and psychological well-being. This study contributes to the conceptual understanding of consumer behavior in the digital era and provides insights for the development of more ethical and reflective marketing practices.